2019
DOI: 10.3390/min9060378
|View full text |Cite
|
Sign up to set email alerts
|

Post-spreading Basalts from the Nanyue Seamount: Implications for the Involvement of Crustal- and Plume-Type Components in the Genesis of the South China Sea Mantle

Abstract: Fresh samples of basalts were collected by dredging from the Nanyue intraplate seamount in the Southwest sub-basin of the South China Sea (SCS). These are alkali basalts displaying right-sloping, chondrite-normalized rare earth element (REE) profiles. The investigated basalts are characterized by low Os content (60.37–85.13 ppt) and radiogenic 187Os/188Os ratios (~0.19 to 0.21). Furthermore, 40Ar/39Ar dating of the Nanyue basalts showed they formed during the Tortonian (~8.3 Ma) and, thus, are products of (Lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Secondly, the comparisons made between these models and the compiled geological evidence are used to provide new constraints on the uncertain Cenozoic tectonics of the region. A map of the relevant regions and geological features for this study is shown in Figure 1 (compiled from Steinshouer et al, 1999;Chung, 1999;Ho et al, 2003;Tang et al, 2006;Choi et al, 2006;Sun et al, 2010;Gong and Chen, 2014;Liu et al, 2001;Yan Q. et al, 2018;Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the comparisons made between these models and the compiled geological evidence are used to provide new constraints on the uncertain Cenozoic tectonics of the region. A map of the relevant regions and geological features for this study is shown in Figure 1 (compiled from Steinshouer et al, 1999;Chung, 1999;Ho et al, 2003;Tang et al, 2006;Choi et al, 2006;Sun et al, 2010;Gong and Chen, 2014;Liu et al, 2001;Yan Q. et al, 2018;Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%